2020
DOI: 10.1177/2455747120913185
|View full text |Cite
|
Sign up to set email alerts
|

Urban Climate Politics in Emerging Economies: A Multi-Level Governance Perspective

Abstract: Several scholars have pointed to the increasing salience of cities in the global endeavour to reduce dangerous climate change to 1.5°C. However, we still lack systematic comparative analyses on how urban climate initiatives evolve in different political-administrative systems of countries in the Global South and what role transnational city networks play in that context. This question is specifically important with regard to the role of cities in contributing to reaching the targets of the Paris Agreement. Aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…To implement large-scale sustainability projects, cities rely on regional and national governments (Homsy & Warner, 2015). In fact, most local governments have limited institutional capacities and financial resources for addressing sustainability (Stehle, Hickmann, Lederer, & Höhne, 2020;Wang, Hawkins, Lebredo, & Berman, 2012). In many cities of the global South where national governments face serious budgetary limitations, effective sustainability actions depend on external funding provided by international agencies or bilateral donors (Nagendra et al, 2018;Stehle, Höhne, Hickmann, & Lederer, 2019).…”
Section: Vertical Integration and Involvement In International Conferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…To implement large-scale sustainability projects, cities rely on regional and national governments (Homsy & Warner, 2015). In fact, most local governments have limited institutional capacities and financial resources for addressing sustainability (Stehle, Hickmann, Lederer, & Höhne, 2020;Wang, Hawkins, Lebredo, & Berman, 2012). In many cities of the global South where national governments face serious budgetary limitations, effective sustainability actions depend on external funding provided by international agencies or bilateral donors (Nagendra et al, 2018;Stehle, Höhne, Hickmann, & Lederer, 2019).…”
Section: Vertical Integration and Involvement In International Conferencesmentioning
confidence: 99%
“…Furthermore, recent studies that assess the degree to which transnational networks and alliances of cities steer their members towards sustainability practices and new organizational structures have come to only modest results (Gordon, 2018;Hickmann, Fuhr, Höhne, Lederer, & Stehle, 2017). Scholars particularly contend that although such networks and alliances offer significant support for many cities, their initiatives often lead to nothing because of constraining factors in the national political-economic system as well as the lack of commitment from mayors and local public officials (Stehle et al, 2020).…”
Section: Transnational Network and Alliancesmentioning
confidence: 99%
“…Our aim in this article is to open this black box by shedding a light on cities’ reasoning for becoming and remaining members of TMNs. The degree of independent authority to engage in TMN activities varies greatly among city governments (Stehle et al, 2020). Even when city governments have the autonomy to set standards and develop independent initiatives, they have limited resources to spend on activities other than delivering core services.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have suggested that support from other levels of government and external private actors is needed to scale up best practices among most cities (Fuhr et al, 2018;Hoppe et al, 2016;Kern, 2019;Wurzel, Moulton, et al, 2019). Nevertheless, support from external private actors to municipal governments has been shown to carry risks; for example, cities might become dependent on and influenced by private agendas and thus lose autonomy (Chu, 2018;Davidson, Coenen, Acuto, & Gleeson, 2019), or a lack of coordination between different actors and government levels could end in actions that mutually counteract one another (Stehle et al, 2020). Overall, the literature in this area consistently states the value of leaders in innovating and developing 'best' practices while also indicating the challenges followers face in scaling up these practices.…”
Section: Methodsmentioning
confidence: 99%
“…We first determine whether a city network works within overarching rules (OR). Polycentric systems are embedded within hierarchical government levels (Dorsch & Flachsland, 2017;Stehle et al, 2020); climate city networks are embedded between the overall climate regime and local governments. The presence or absence of these overarching rules directly influences the evolution of a polycentric system in terms of autonomous decisionmaking of its members and their self-organization (Thiel & Moser, 2019).…”
Section: Understanding City Network Diversitymentioning
confidence: 99%